2009
DOI: 10.1161/atvbaha.108.180950
|View full text |Cite
|
Sign up to set email alerts
|

Fibrinogen-γ C-Terminal Fragments Induce Endothelial Barrier Dysfunction and Microvascular Leak via Integrin-Mediated and RhoA-Dependent Mechanism

Abstract: Objectives-The purposes of this study were to characterize the direct effect of the C-terminal fragment of fibrinogen ␥ chain (␥C) on microvascular endothelial permeability and to examine its molecular mechanism of action. Methods and Results-Intravital microscopy was performed to measure albumin extravasation in intact mesenteric microvasculature, followed by quantification of hydraulic conductivity in single perfused microvessels. Transendothelial electric resistance was measured in microvascular endothelial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
31
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 31 publications
(32 citation statements)
references
References 46 publications
1
31
0
Order By: Relevance
“…Fibrinogen deposition with or without conversion to fibrin increases inflammation and vascular permeability where it is deposited (18,19). Increased levels of fibrinogen alter vascular reactivity and impair endothelial cell layer integrity by binding to endothelial cell membrane receptors (17,31). Taken together, the Aβ-fibrinogen interaction could reduce fibrin degradation and induce fibrinogen deposition in blood vessels.…”
Section: Discussionmentioning
confidence: 99%
“…Fibrinogen deposition with or without conversion to fibrin increases inflammation and vascular permeability where it is deposited (18,19). Increased levels of fibrinogen alter vascular reactivity and impair endothelial cell layer integrity by binding to endothelial cell membrane receptors (17,31). Taken together, the Aβ-fibrinogen interaction could reduce fibrin degradation and induce fibrinogen deposition in blood vessels.…”
Section: Discussionmentioning
confidence: 99%
“…The β5 subunit of integrins has been identified as a key molecule involved in the recruitment of kinases to focal adhesions in endothelial cells upon stimulation by vascular endothelial growth factor (VEGF) (Avraham et al, 2003), and mice deficient in β5 integrin display a reduced vascular permeability response to the growth factor (Eliceiri et al, 2002). Most recently, an in vivo experiment demonstrated that plasma leakage across microvessels in the presence of fibrinogen degradation products is greatly attenuated in β1 integrin knockout mice (Guo et al, 2009), further supporting a role for integrins in mediating endothelial hyperpermeability.…”
Section: Endothelial Barrier Structurementioning
confidence: 96%
“…In endothelial cells during stimulation by inflammatory agents, actin polymerization and stress fiber formation occur concomitantly with myosin light chain phosphorylation (Yuan, 2000). These cytoskeletal responses act in concert producing a centripetal contractile force that competes cell-cell adhesions rendering widened intercellular space (Guo et al, 2009; Huang et al, 2003; Reynoso et al, 2007; Sun et al, 2006; Tinsley et al, 2004; Yuan et al, 2002). …”
Section: Endothelial Barrier Structurementioning
confidence: 99%
“…So far, only one molecular target has been reported to mediate this effect, namely vascular-endothelial-cadherin, an anchor protein that is part of the tight junctions and thus directly responsible for endothelial leak tightness (Petzelbauer et al 2005). Even fibrinogen and fibrin monomers are able to bind to ICAM-1 on ECs and thereby promote the attachment of leukocytes and platelets which in turn may then result in vascular occlusion (Altieri et al 1995) strong vasoconstriction by the stimulation of ET-1 (Anggrahini et al 2009), or resulting in paracellular hyperpermeability and subsequent fluid and protein leak via RhoAdependent signaling pathways (Guo et al 2009). …”
Section: Fibrin Degradation Productsmentioning
confidence: 99%